Pengembangan Life Skill Melalui Program Pendidikan Lapak Baca di Kelurahan Penggaron Kidul Kecamatan Pedurungan Kota Semarang - Suprihatiningsih; Eko Handoyo; Juhadi; Raudhah Setya; Endah Septiani; Dewi Aryanti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
The issue of education is a right that is agreed to be the main thing. Education is the key to development and developing human quality in the form of increasing competence. It is hoped that education will be able to face challenges and changes in the present and future. However, in reality there are still people who cannot get education due to costs or other reasons. The focus of this research is to find out (1) What is the process of developing Life Skills through the reading stall program in Penggaron Kidul Village, Pedurungan District, Semarang City. (2) What are the results of developing Life Skills through the reading stall program, Pengaron Kidul Village, Pedurungan District, Semarang City. This research uses qualitative methods with the type of field research. Data collection techniques include interviews, observation and documentation. The research data sources are primary and secondary data. Data analysis techniques include: (1) Data Reduction. (2) data presentation. (3) conclusion. The results of this research show that 1) the process of developing Life Skills through the reading stall program in Penggaron Kidul Village, Pedurungan District, Semarang City is carried out with various activities including: (a) Preparation Stage (b) Assessment Stage (c) Alternative program planning stage. (d) action plan stage (f) Program Implementation Stage (g) Evaluation Stage. (h) Termination Stage 2). The results of developing Life Skills through the reading stall program, Penggaron Kidul Village, Pedurungan District, Semarang City include, (a) Personal aspects, namely the development of the abilities of the community, being able to identify the potential they have, the community being able to solve problems independently, as well as having a positive influence on children. can be independent, creative, innovative, disciplined, responsible, civilized, polite and have good morals. (b) social aspects include sensitivity to the surrounding environment, taking part in community activities, children's attitudes that are no longer individualistic with cooperation always implemented so that reciprocal communication occurs. (c) academic aspects, developing reading and writing skills for illiterate people. developing community insight and fulfilling formal education for out-of-school children with study guidance, critical thinking skills, the ability to express opinions and public speaking to the general public with clear sources, namely reading materials and activities carried out in the reading stall program. (d) vocational aspects are demonstrated by various directions through community entrepreneurship training, having online marketing skills for MSME products and exploring talent interests, skills in the art of music for children and teenagers, namely with Drumband.